Trans-generational effects of prenatal stress in quail - Guibert, Floriane (The Royal Society, 2013)
The prenatal environment is a source of phenotypic variability influencing the animal's characteristics. Prenatal stress affects not only the development of offspring, but also that of the following generation. Such effects have been best documented in mammals but can also be observed in birds, suggesting common processes across phylogenetic orders. We found previously that Japanese quail females stressed during laying produced offspring with higher fearfulness, probably related to modulation of testosterone levels in their eggs. Here, we evaluated long-term effects of prenatal stress by analysing reproductive traits of these F(1) offspring and, then, the development of their subsequent (F(2)) offspring. The sexual behaviour of F(1) prenatally stressed (F1PS) males was impaired. F1PS females' eggs contained less yolk and more albumen, and higher yolk testosterone and progesterone levels than did F(1) prenatal control females. The fearfulness of F(2) prenatally stressed quail was greater than that of F(2) prenatal control quail. These F(2) behavioural differences paralleled those evidenced by their parents, suggesting trans-generational transmission of prenatal stress effects, probably mediated by egg compositions of F1PS females.